Examining the teaching competencies of public elementary school teachers: Extent and differences across profiles - Balabal, Henry Jr.; Canuto, Peter Paul (Journal of Interdisciplinary Studies in Education, 2026)
Teaching competency is vital for quality education, enabling teachers to provide effective instruction and support holistic student development. This study assessed the extent of agreement among 65 public elementary school teachers in Ifugao, Philippines, regarding their teaching competencies and examined variations across their demographic profiles. A quantitative descriptive survey was employed using the Teaching Competency Evaluation for Elementary Teachers (TCEET), which assessed five domains: professionalism, teaching effectiveness, instructional planning, classroom management, and adaptability. The results reveal that teachers rated their competencies to a very great extent, with professionalism rated highest. Gender differences emerged solely in instructional planning, favoring males. Age differences appeared in professionalism and teaching effectiveness, with younger and older teachers rating higher.